2009
DOI: 10.1371/journal.pone.0008005
|View full text |Cite
|
Sign up to set email alerts
|

Transposition and Intermingling of Gαi2 and Gαo Afferences into Single Vomeronasal Glomeruli in the Madagascan Lesser Tenrec Echinops telfairi

Abstract: The vomeronasal system (VNS) mediates pheromonal communication in mammals. From the vomeronasal organ, two populations of sensory neurons, expressing either Gαi2 or Gαo proteins, send projections that end in glomeruli distributed either at the rostral or caudal half of the accessory olfactory bulb (AOB), respectively. Neurons at the AOB contact glomeruli of a single subpopulation. The dichotomic segregation of AOB glomeruli has been described in opossums, rodents and rabbits, while Primates and Laurasiatheres … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…This has been reported in opossums, tenrecs, rabbits, mice, rats, sheeps and dogs (McCotter, 1912; Imamura et al. 1985; Wekesa & Anholt, 1999; Suárez et al. 2009).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…This has been reported in opossums, tenrecs, rabbits, mice, rats, sheeps and dogs (McCotter, 1912; Imamura et al. 1985; Wekesa & Anholt, 1999; Suárez et al. 2009).…”
Section: Discussionmentioning
confidence: 54%
“…The AOB of muroid rodents (e.g. mice, rats and hamsters) is a lentiform structure with rAOB and cAOB subdomains of similar form and size, and as all other mammals outside Caviomorpha (South American members of the Hystricognathi rodent sub‐order), it receives vomeronasal innervation from the medial aspect (McCotter, 1912; Wekesa & Anholt, 1999; Suárez et al. 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In the VNO of opossum and tenrec, the Gα i2 ‐and Gα o ‐mediated dual vomeronasal pathways are present (Halpern et al,1995; Suárez et al,2009) (Table 2), suggesting that the presence of the dual vomeronasal pathways is a basal condition for mammals. However, in goat, horse, musk shrew, and marmoset, the V2R‐Gα o vomeronasal pathway seems to have deteriorated and the uniform‐type Gα i2 ‐mediated vomeronasal pathway is functional (Takigami et al,2004) (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…However, subsequent reports showed that Primates and Laurasiatherians do not show this dichotomous segregation, such that either they possess the V1R pathway only (such as in goats, marmosets, shrews, domestic carnivores, elephants and hippopotami) or no vomeronasal system at all (such as in apes, some bats and aquatic species; Meisami & Bhatnagar, 1998;Takigami et al 2000Takigami et al , 2004Ngwenya et al 2011;Zhao et al 2011;Kondoh et al 2017). Moreover, the lesser Tenrec (Echinops telfairi), a basal Afrotheria, has a dichotomous but not strictly segregated VNS (Su arez et al 2009b), while the hyrax (Procavia capensis), another basal Afrotheria, possesses the V1R pathway only (Su arez et al 2011a). Furthermore, not all rodents have a dichotomous VNS; the California ground squirrel (Otospermophilus beecheyi), a sciurid rodent, has the V1R pathway only (Su arez et al 2011a).…”
Section: Introductionmentioning
confidence: 99%